Three year survival among patients with aids-related Kaposi sarcoma treated with chemotherapy and combination antiretroviral therapy at Moi teaching and referral hospital, Kenya - Busakhala, Naftali; Kigen, Gabriel; Waako, Paul; Strother, Matthew R.; Chite, Fredrick; Loehrer, Patrick (Infectious agents and cancer, 2019)
AIDS-related Kaposi sarcoma (AIDS-KS), a common malignancy in Kenya is associated with high morbidity and mortality. AIDS-KS is treated using bleomycin and vincristine (BV) plus or minus doxorubicin in most low resource settings, with response rates ranging from 24.8 to 87%. Survival in low resource settings has not been well documented. We report the three-year survival in a cohort of seventy patients referred to Moi Teaching and Referral Hospital (MTRH). Methods: Study participants are part of a randomized phase IIA trial on the use of gemcitabine compared to bleomycin plus vincristine for the treatment of Kaposi sarcoma after combination antiretroviral therapy (cART) in Western Kenya. All patients were followed for three years in MTRH. Survival was determined by three monthly physical examination and analysed using Kaplan-Meier method, while possible determinants of survival such as baseline characteristics, type of chemotherapy, initial CD4 counts, age at enrolment, gender and early response to chemotherapy were analysed using univariate and multivariate Cox regression.
Keywords: AIDS-related Kaposi; sarcoma; Survival; Kenya